Linear increase in the number of non-pulmonary vein triggers from paroxysmal to persistent and long-standing persistent AF in patients undergoing repeat procedure after successful isolation of pulmona. (14th October 2021) - Mohanty, S; Trivedi, C; Della Rocca, D G; Gianni, C; MacDonald, B; Mayedo, A; Burkhardt, J D; Bassiouny, M; Gallinghouse, G J; Horton, R; Al-Ahmad, A; Di Biase, L; et al.
Abstract: Introduction: This study evaluated the prevalent triggers responsible for recurrence following successful PVI in different types of atrial fibrillation (AF). Methods: Consecutive AF patients undergoing repeat catheter ablation with permanently isolated PV were included in the analysis. High-dose isoproterenol challenge (20- 30μg/min for 15–20min) was used to confirm PV reconnection and identify non-PV triggers. Circular mapping catheter (CMC) was used to map the site of origin of significant ectopic activity by comparing the activation sequence of the sinus beat with that of the ectopic beat. For the coronary sinus (CS), ablation catheter was positioned at the level of the mitral valve annulus, parallel to the one positioned in the CS. Left atrial appendage (LAA) firing was detected by placing the CMC in the left superior PV and thus recording far-field potentials from the LAA. Results: This prospective study included 1850 AF patients undergoing repeat AF ablation (Table 1), of which 573 (31%) had received one and the remaining 1277 patients had received 2 earlier ablations. Permanent PVI was confirmed with isoproterenol challenge. Table 1 shows the distribution of non-PV triggers. A linear increase in the number of non-PV triggers was observed from PAF to PerAF to LSPAF. Significantly higher number of LSPAF patients had detectable non-PV triggers compared to PerAF and PAF cases. Conclusion: We observed a linear increase in the number of non-PV triggers in PAF to PerAF and LSPAF patients experiencing recurrence with successful isolation of PVs. As non-PV triggers are often not targeted by operators, this could be the underlying mechanism for more frequent recurrences in non-paroxysmal AF. Funding Acknowledgement: Type of funding sources: None.